Pendidikan dan Pelatihan Santri Siap Guna (SSG) untuk Meningkatkan Religiusitas Santri Daarut Tauhiid - Gusti Lara Ekamia; Agus Abdul Rahman; Ila Nurlaila Hidayat (Jurnal Psikologi Islam dan Budaya, 2023)
Religiosity is an important factor in human life, so various ways are needed to increase this religiosity. This study aims to determine the effect of Santri Siap Guna (SSG) education and training on the religiosity of Daarut Tauhiid students. This study used a quantitative approach to the pre-experimental method with the type of one group pretest-posttest design. There were 101 participants who received treatment in the form of education and training for three months through three stages, namely: self-challenge stage, self-development stage, and team and organization development stage. Data collection used the scale of religiosity. The results show that the Santri Siap Guna (SSG) education and training had an effect on the religiosity of the Daarut Tauhiid students.